The Effectiveness of Using Social Media as a Tool of Public Relations Communication at the Tamala Regency DPRD Office - Muh. Akbar; Risma Niswaty; Isgunandar Isgunandar (Asha Publishing, 2025)
The development of information technology has brought major changes in various aspects of life, including in the way of communication. The government and public institutions have begun to use social media to disseminate information, educate the public, and receive input and complaints effectively and faster. However, the use of social media as a communication tool for Public Relations certainly has challenges. These challenges include strategies for managing the dissemination of information so that the message conveyed can be well received by various circles of society. This study discusses the effectiveness of the use of social media as a communication tool for Public Relations in the Bakalar Regency DPRD office. This study uses a qualitative approach with a descriptive type of research. Data were collected through observation, interviews, and documentation, and analyzed using data presentation, data condensation, and conclusion drawing techniques. The results of the study show that the effectiveness of the use of social media as a communication tool for Public Relations at the Takalar Regency DPRD office is considered less effective which is measured through four indicators, namely the attractiveness of social media is increased by presenting more varied and interesting content. The clarity of information conveyed through social media is enhanced through an orderly structure and the use of easy-to-understand language. The completeness of information requires more relevant content for the public in order to provide ease of access to the Takalar Regency DPRD's social media which utilizes social media platforms in disseminating information